Analisis Strategi Pengembangan SDM untuk Meningkatkan Mutu Pendidikan dan Minat Calon Siswa SMAN 11 Denpasar - Ni Komang Gek Tika Purnama Wati; Putu Irma Yunita (Ikatan Da'i Indonesia, 2025)
Education is a key pillar in developing quality human resources. Schools, as formal educational institutions, play a strategic role in creating a competent and virtuous future generation. However, in the era of globalization and increasingly fierce competition, schools are required to continuously improve the quality of education and their competitiveness. The issue of facilities and infrastructure is one of the critical factors influencing prospective students' interest in enrolling at SMA Negeri 11 Denpasar. An interview with the Principal, I Ketut Suwita, S.Pd., M.Pd., revealed that